НАРОДНИТЕ ВЕРУВАЊА КАКО ДЕЛ ОД СЕКОЈДНЕВНИОТ ЖИВОТ: (ПРЕКУ ПРИМЕРИ ОД МАКЕДОНСКАТА ПРОЗА) (Filološke studije, 2019)
Different beliefs were always a part of people’s everyday life. Therefore, some of the most wide-spread folk beliefs among Macedonian people contained in the novels Krpen Zhivot, Razboj, Pirej and Nebeska Timjanovna, as well as in the story Bojana, are examined in this paper. Beliefs in sorceresses, the Fates, fortune-telling powers, multiple meanings of dreams, magical rituals, things and potions, as well as beliefs in the magical function of words all of which are regularly present in people's lives in times of war, social changes and turmoil, when a person is faced with dis- eases, hunger, the death of people close to him,, when he feels hurt, threatened or left on his own, get a different meaning. They become a way and a tool for dealing with desperate situations. At the same time, the beliefs in the invisible powers that can help when nothing else can, remain the only hope that the person can survive even in impossible circumstances. These rituals and beliefs have a very long tradition, especially in a patriarchal society. They are a part of the world view of the people, and are performed in a certain order and at certain times. They are learned and practiced as everyday house chores, the same way the work on the fields and around the cattle are learned. Their role in everyday life in general, as well as in specific segments, is of essential significance.